Spherical aromaticity of inorganic cage molecules - Hirsch, Andreas; Chen, Zhongfang; Jiao, Haijun (Angewandte Chemie International Edition, 2001)
Not only fullerenes but also inorganic cage molecules can be highly spherical aromatic. The molecular allotropes 1 (E = N, P, As, Sb, Bi) of the Group V elements and a variety of Zintl anions are even double spherical aromatic and obey the 2(N + 1) rule, since both their σ and π shells are completely filled. This is reflected by a pronounced diatropic character.